SM Analytics: Impact of SM Engagement Metrics on Online Purchase Intention - Rahman, Z.; Kumaran, S.; Zanuddin, H.; Nasir, M.H.N.M. (Medwell Journals, 2017)
Online sale is now the most targeted and striking selling strategy for most of the business enterprises. SM (Social Media) now is the most attractive segment to attract consumers and to contact them directly. Many researches have been conducted on identifying the importance of SM on purchase intention. In social media, users tend to do different types of activities, (e.g., comment, like, share, view) and these users actions create SM (Social Media) engagement metrics. Users of different Facebook fanpages tend to engage with different pages in different ways. Marketers definitely now need to explore the actual impact of social media engagement activities on online purchase intension and also they need to find out the consistency of online sales with social media engagement metrics. But yet no study explored the relationship of different user’s engagement actions with online purchase intention. The study is based on an online survey conducted on Malaysian social media users (n = 410) to explore their purchase intention alongside their engagement activities. It will help the E-commerce marketers to identify the importance level of social media engagement metrics on online sales and also guide the e-marketers to decide on e-marketing tools to be encouraged particularly for engagement metrics to make online sales. A survey was conducted among the social media users and responses were recorded using the University of Malaya survey portal. Data was analysed using AMOS 23 and a best fitted model is suggested to be implemented in social media marketing policy. The study reveals a strong positive relationship between fanpage engagement metrics and online purchase intention. The results will guide ecommerce marketers identify the significance of social media engagement on online sales while helping emarketers on their decision pertaining to e-marketing tools, particularly for engagement metrics in increasing online sales.